The Application of Various Fermented Malang Apple Water As A Source of Natural Yeast for Sourdough Bread Processing - Hanif Alamudin Manshur; Desiana Nuriza Putri; Okta Pringga Pakpahan; Qq Wima Akalentera; Noor Harini (Indonesian Association of Food Technologists, 2023)
The sourdough fermentation method is identified as a complex microbial ecosystem stimulant by the spontaneous natural water starters process. At the fermentation time, lactic acid bacteria and yeast confer the resulting characteristic bread features such as staling of bread, and palatability. With the scope of highlighting fermentation, the investigation of starter culture is relevant in order to determine starch fractions of flour. The present article employed water from apple local varieties of Malang as a mixture of natural yeast. The research was conducted in two stages. The first stage was to get the best apple variety to produce the optimum quality of sourdough starter. The second was applying the best sourdough starter at various concentrations in bread formulation. Parameters observed included yeast, and lactic acid bacteria counts, pH, Total Titratable Acidity (TTA), lactic acid content, hardness, loaf volume, specific volume, and sensory properties of sourdough bread. There was an influence on the treatment of making a sourdough starter with different types of apple fruit and showed the best treatment if sourdough starter of fermented manalagi apple water with a pH value of 4.5, TTA value of 2.71 mL, the number of lactic acid bacteria of 5.6 × 1010 CFU/mL, and the number of yeast of 2.62 × 1011 CFU/mL.